2012
DOI: 10.1111/iej.12031
|View full text |Cite
|
Sign up to set email alerts
|

The expression and role of Lysyl oxidase (LOX) in dentinogenesis

Abstract: The data indicate that LOX is not essential in dentinogenesis, even though LOX deletion may affect dentine matrix collagen thickness and packing. The absence of functional LOX may be compensated by LOX isoenzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…During embryogenesis and organ development, LOXs promote infrastructural integration, in addition to facilitating the proper cell stiffness and rigidity required for organogenesis and subsequent morphological maintenance (17,(20)(21)(22)(23). That is, the cells can be secured and maintained properly in the organic mesh and are able to maintain their functional polarity (12).…”
Section: Roles Of Members Of the Lox Family In Organ Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…During embryogenesis and organ development, LOXs promote infrastructural integration, in addition to facilitating the proper cell stiffness and rigidity required for organogenesis and subsequent morphological maintenance (17,(20)(21)(22)(23). That is, the cells can be secured and maintained properly in the organic mesh and are able to maintain their functional polarity (12).…”
Section: Roles Of Members Of the Lox Family In Organ Developmentmentioning
confidence: 99%
“…The development of teeth has been found to involve ECM condensation and odontogenic stabilization (36), of which both processes can be observed through densely packed collagen fibers and orderly polarized picrosirius red staining. Through investigating odontogenesis, Tjaderhane et al (22) identified no significant differences among the teeth of LOX -/-, LOX +/and wild-type mice under the light microscope; however, following histochemical examination, the teeth of the LOX -/and LOX +/mice were observed to be thinner and unpolarized, which indicated that these effects may be due to the dysregulation of LOX. Kim et al (37) demonstrated that both LOX and LOXLs were essential for organizing periodontal ECM fibrogenesis and promoting the differentiation of dental pulp cells from odontoblasts.…”
Section: Roles Of Members Of the Lox Family In Organ Developmentmentioning
confidence: 99%